Severe Combined Immune Deficiency- An Ayurvedic Aspect with reference to Anuvanshik Vyadhi and Oja Kshaya (AYUSHDHARA, 2022)
The bubble boy disease is also known as SCID (Severe Combined Immune Deficiency) is a very rare genetic disorder, affects approximately 50-100 children in the United States every year. In India, before 2000 no case of SCID is diagnosed which is due to lack of awareness and diagnostic facilities. A steady increase in the number of diagnosed cases was found in India over the last 8 years. SCID is also known as Swiss-type Agammaglobulinemia which is characterized by disturbed development of B cells and T cells resulting in a weak immune system and recurrent infections. In Ayurveda, as such, no disease is compared with SCID, but it can be correlated with Anuvansik Vyadhi or Sahaja Vyadhi i.e., inherited disorder which results in Sahaja Oja Kshaya (primary immune deficiency). Aim: The present study aimed to understand the Ayurvedic perspective of SCID with reference to Anuvanshik Vyadhi, Oja Kshaya, and its probable treatment as per Ayurveda. Materials and methods: Brahitri, Laghutrayi, Nighantus, and various databases like Google Scholar, PubMed, DHARA, Scopus, Science Direct were searched with research papers that help to co-related SCID in Ayurvedic perspective and to understand its cause, treatment as per Ayurveda. It was found that SCID is a primary immunodeficiency disorder that is very severe that occurs due to mutation in ten different known genes and results in a highly compromised immune system that is considered almost absent. This bubble boy disease is considered fatal without corrective gene therapy or stem cell transplant according to modern perspective but with a proper understanding of the cause and symptoms of SCID, the Ayurvedic line of treatment can give miraculous results in SCID. Conclusion: SCID is Anukata Vyadhi as per Ayurveda, but with the use of various Ayurvedic lines of treatment like Shodhana (purification therapy), Suvarna Prashan, various herbs, SCID diseases can be prevented from occurrence and help to improve the quality of life of people suffering from SCID.